2009
DOI: 10.1103/physrevlett.102.033004
|View full text |Cite|
|
Sign up to set email alerts
|

Angular Tunneling Ionization Probability of Fixed-in-SpaceH2Molecules in Intense Laser Pulses

Abstract: Angular tunneling ionization probability of fixed-in-space H₂ molecules in intense laser pulsesWe propose a new approach to obtain molecular frame photoelectron angular distributions from molecules ionized by intense laser pulses. With our method we study the angular tunnel ionization probability of H 2 at a wavelength of 800 nm over an intensity range of 2-4:5 Â 10 14 W=cm 2 . We find an anisotropy that is stronger than predicted by any existing model. To explain the observed anisotropy and its strong intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(66 citation statements)
references
References 38 publications
4
62
0
Order By: Relevance
“…Alternatively, PMDs can be measured in a reaction microscope [22], where information on the molecular orientation is obtained by electron-ion coincidence. For molecular imaging, circularly polarized light effectively delivers a 360°scan of the aligned molecule [23][24][25], which is an advantage over linear polarization. In the classical trajectory model without Coulomb effects, electrons measured at an emission angle ϕ originate from ionization at the angle ϕ AE 90°with the sign depending on the rotation direction of the field.…”
mentioning
confidence: 99%
“…Alternatively, PMDs can be measured in a reaction microscope [22], where information on the molecular orientation is obtained by electron-ion coincidence. For molecular imaging, circularly polarized light effectively delivers a 360°scan of the aligned molecule [23][24][25], which is an advantage over linear polarization. In the classical trajectory model without Coulomb effects, electrons measured at an emission angle ϕ originate from ionization at the angle ϕ AE 90°with the sign depending on the rotation direction of the field.…”
mentioning
confidence: 99%
“…Figure 2 shows the calculated ratio P /P ⊥ and the experimental values [22]. Note that the laser intensity of the experiment is divided by 2 since a circularly polarized laser was used in the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Recently Staudte et al [22] measured the angular tunneling ionization probability of H 2 molecules using a circularly polarized 800 nm intense laser and found that the ratio P /P ⊥ varies as a function of laser intensity. The measured ratio is generally larger than that predicted by the MO-ADK theory, which does not depend on the laser intensity nor on the wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…AmmosovDelone-Krainov (ADK) theory [3], which is often applied to atoms to compare the absolute values and electric field dependence of ionization rates between theory and experiment, has been extended to treat molecular systems (the molecular ADK model) [14,15]. A qualitative consequence of the molecular ADK model is that the TI rate reflects the geometric structure of the HOMO [16][17][18][19][20]. We can make the physical interpretation that photoelectrons are much more likely to be extracted via tunnelling from the large-amplitude lobe of the HOMO in the opposite direction of the electric field vector.…”
Section: Introductionmentioning
confidence: 99%